Chapter When Paul Met Ludwig Wittgensteinian Comments on Boghossian's Antirelativism - Kusch, Martin (De Gruyter, 2017)
This paper tries to make plausible the following claims: The paragraphs §608-612 of "On Certainty" do not speak in favour of what Boghossian construes as the Master Argument for Relativism; that "On Certainty" introduces various relativistic themes; and that Boghossian and Wittgenstein conceptualize epistemic systems in rather different ways that lead to very different views on three candidate cases for radical difference in epistemic systems.